Using games for social learning to promote self-governance - Janssen, Marco A.; Falk, Thomas; Meinzen-Dick, Ruth S.; Vollan, Björn (Elsevier, 2023)
Governance of shared resources needs to overcome collective action problems. Relational values and decision-making play a critical role in this process. Approaches are needed to stimulate self-governance, taking relational values into account. We review the literature on the use of collective action games as a tool to stimulate social learning and self-governance. We emphasize the importance of legitimacy in decision-making and the risk of crowding out internalized motivations — for instance, based on relational values — with instrumental incentive mechanisms. We further highlight the need to include ecological outcome indicators in the game design to allow the activation of relational values. Our review concludes that games used as part of a set of participatory activities enable communities to come together to identify relevant problems and craft potential solutions.